Application of Pectin Extracted from Pomelo Peel in Making of Pomelo Jam (Citrus maxima L.) - Humairah H; Mulyati M Tahir (Universitas Teuku Umar, 2021)
Pomelo has many benefits as a potential fruit in South Sulawesi therefore they can be processed into a variety of products; one of them is pomelo jam. In this research, pomelo peel was utilized into pectin then applied on to a pomelo jam. The aim of this study was to determine characteristics of pectin from pomelo peel, by looking at the effect of pomelo peel pectin on a pomelo jam, and selected formulation in making of pomelo jam. Pectin was extracted from pomelo peel powder using distilled water and HCl. The filtrate was precipitated using 95% ethanol, rinsed, then dried. Pectin was characterized and applied to pomelo jam. Pomelo jam was made with soaking, boiling, and pulverization. Pomelo pulp was heated then sugar and pectin were added according to the formulation. Parameters on jam observed included organoleptic aspects, spreadability, moisture content, total soluble solids (TSS), vitamin C, and crude fiber. Pectin from pomelo was typically low methoxyl pectin and low degree of esterification (<50%). Panelists were preferred pomelo jam for G1P1 formulation (33% sugar; 0.3% pectin) with a score of 5 (slightly liked) out and score 3 (smooth) for spreadability. The water content of pomelo jam was 23-30%, TSS was 39.47-560Brix, vitamin C ranged from 0.004-0.006%, and crude fiber was 0.96%-1.20%. Characteristics of pomelo peel were low methoxyl, low methyl ester, the equivalent weight of 627.64 mg, and galacturonic acid 212.61%. Interaction between concentration of sugar and pectin had a significant effect on TSS, while the concentration of sugar had a significant effect on aroma, spreadability, and moisture content, whereas the concentration of pectin had no significant effect on jam parameters. A combination of 0.3% pectin and sugar 33% was the selected formulation in making pomelo jam.